Targeted next-generation sequencing for antimicrobial resistance detection in ventilator-associated pneumonia - Yuting Li; Yanfang Jiang; Hao Liu; Yao Fu; Junying Lu; Hongyan Li; Lulu Sheng; Dejian Gu; Dong Zhang (Frontiers in Cellular and Infection Microbiology)
BackgroundVentilator-associated pneumonia (VAP) carries a high mortality rate in the intensive care units (ICUs) due to its widespread drug resistance. Traditional microbial cultures limited by speed and sensitivity, are often unable to help clinicians make effective diagnosis and treatment. Therefore, there is an urgent need for a rapid and accurate test that can identify both pathogens and their antimicrobial resistance (AMR) to improve the prognosis of patients with VAP.Study designWe analyzed samples from ICU patients with suspected VAP using both microbial tests and targeted next-generation sequencing (tNGS), comparing the results of tNGS pathogen and AMR detection against microbial culture and antimicrobial susceptibility testing (AST).ResultsInvolving 199 patients with suspected VAP, tNGS showed a sensitivity rate of 98.98% for pathogen identification. While the sensitivity rate of microbial culture was just 66.84%. Additionally, tNGS performed almost half the turnaround time of microbial culture (1.66 days vs 3.00 days). For AMR, the overall consistency between AST and tNGS was 79.31%. The great performance particularly exhibited for Acinetobacter baumannii carbapenem-penicillin-cephamycin resistance.ConclusiontNGS excels in identifying pathogens and AMR. Its rapid workflow makes it ideal for managing critically ill patients, enhancing treatment precision, and reducing antibiotic misuse.